Perhitungan Nilai Ekonomi Total dalam Rangka Pemanfaatan Ruang Wilayah pulau Kalimantan - Ruchyat Deni Djakapermana; Santun R.P. Sitorus; Marimin Marimin; Ernan Rustiadi (Journal of Regional and City Planning, 2005)
Total  economic  value  is  considered  as  a  useful  tool  for  analyzing objectively the change of economic level in    certain area as a consequence of  changing  on  the  different  policies  of  regional  development  based  on regional  spatial  plan.  Results  calculation  on  the  application  of  total economic  value  approach  in  Kalimantan  region,  shows  that  the  total economic  values  calculated  based  on  conservation  scenario   (Scenario  A) and  do  nothing  scenario  (Scenario  B) are about 2.065,22 trillion Rupiah, and  1.695,83 trillion  Rupiah,  respectively.  The  Benefit  Cost  Ratio (BCR) for scenario A (9,91) is higher than BCR for scenario B (3,44). This calculation gave an  indication  that  comply  with the previous  premise  that regional  development  in  Kalimantan  region  should  be  based  on  regional spatial  plan  for  Kalimantan  region.  Therefore,  it  is  recommended  that development  control  to  make sure  that  developments  comply  with  the regional spati al plan should be applied wisely and consistently.Keywords: Kalimantan spatial plan, total economic values, benefit-cost ratio